Pengelolaan Pembelajaran Ipa Berbasis MultimediaDi Smp Negeri 1 Purwodadi - SUTIKNYO, SUTIKNYO, Prof. Dr. Sutama, M.Pd (2016)
Abstract: The purpose of the study (1) determine the planning multimedia-based learning science in SMP Negeri 1 Purwodadi. (2) investigate the implementation of multimediabased learning science in SMP Negeri 1 Purwodadi. (3) determine the evaluation of multimedia-based learning science in SMP Negeri 1 Purwodadi. Data collection techniques are observation, interview, documentation. Data analysis techniques of data reduction, data presentation, and conclusion. Test the validity of triangulation.The results of the study (1) Planning IPA multimedia-based learning in SMP Negeri 1 Purwodadi ie Teachers prepare lesson plans to make power point, video, students' worksheets. Supporting facilities including LCD, science laboratory, a laptop, an internet connection. (2) Teachers do apersepsi, explanation learning objectives, delivery of content through power point and video ends of students work on the problems. Learning conducted in laboratories, classrooms, (3) evaluation of the learning takes place every end of the lesson, each material in the KD resolved, each pertengan semester and end of each semester. Problem multiple choice and essay, about 45-60 minutes. With the IPA pembelajaan multimedia-based learning outcomes of students increased to KKM mata pelajaran IPA in each class reach 85-90% already completed studies. Compared to prior use of multimedia mastery learning students is 75-80%. Follow-up of the evaluation results obtained are schools doing repairs without stopping, especially in improving the process of learning, enrichment materials and infrastructure. Keywords: learning management,science learning multimedia